Analisis komunikasi persuasif dalam mengubah perilaku masyarakat (studi kasus penyelesaian konflik di kelurahan manggadua kota ambon) - Sandra I. Telussa; Johana Nahuway; Renata Radinka; Marliano Try Yoel Rumpeniak (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
Persuasive communication plays a vital role in shaping and transforming community behavior, particularly in resolving social conflicts within communities characterized by complex social dynamics such as Manggadua Village in Ambon City. This study aims to analyze the forms, strategies, and effectiveness of persuasive communication employed by community leaders in resolving conflicts and influencing social behavior change. Using a descriptive qualitative approach, data were collected through in-depth interviews with community leaders, mediators, and residents directly involved in conflict resolution processes. The findings reveal that persuasive communication is implemented through three main approaches: emotional, rational, and social, which have proven effective in fostering empathy, logical awareness, and social solidarity. These approaches collectively contribute to reducing conflict intensity and strengthening a culture of dialogue among community members. The study provides theoretical insights into the development of conflict communication studies and practical contributions for local governments and stakeholders in designing effective communication strategies to build sustainable peace at the community level.